Reducing Older Generations’ Apprehension Toward QRIS in Traditional Markets: A Visual Communication Approach - DIAN FITRIARNI SARI; Rizky Alfadly; Amy Maulid; Yasha Langitta Setiawan; Deby Gemysa Faradiba (fakultas Desain Komunikasi Visual, 2026)
The adoption of QRIS in traditional markets remains uneven, particularly among older generations who experience low digital literacy and high levels of technology anxiety. These barriers are not solely technical but are strongly influenced by psychological factors such as fear of making transaction errors and lack of trust in digital payment systems. This study aims to develop a visual communication strategy to reduce apprehension and improve QRIS adoption among elderly users in traditional market settings. This research employs a qualitative approach using AIDA (Attention, Interest, Desire, Action) model to identify key issues derived from interviews, observations, and open-ended questionnaires. The findings are then translated into design solutions using the AIDA model as a framework for structuring communication strategies. The results indicate that visual communication design plays a significant role in bridging the gap between technological complexity and user understanding. By applying clear visual hierarchy, simplified information flow, trust-building messages, and step-by-step instructional visuals, the proposed design effectively addresses cognitive and emotional barriers. The study concludes that a behavior-oriented visual communication approach contributes to enhancing perceived ease of use and user confidence, reducing technology anxiety, and strengthening behavioral intention to adopt QRIS.